Exploring Effective Factors on Football Games Watching Decisions of Individuals: The Role of Entertainment Value and People's Characteristics in Watching Games - Cavdar, Nilsah; Kircova, Ibrahim (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2018)
The present study provides a new approach to the subject of spectator behaviors in sports marketing, a contemporary area of marketing. In this study, the decision to watch football games has been categorized as follows: watching in a stadium, watching at home, watching with a community and not watching. The aim of the study is to discover people's perceptions of entertainment value of football and characteristics of people in relation to football, and other key elements behind these individuals' decisions of watching games, in different categories. For this purpose, in-depth interviews were conducted with 20 people (5 for each group) and the data gathered from these interviews were analyzed through NVivo 11. According to the research findings, the entertainment value for football is high for the spectators who watch games in stadiums, average for the audience who watch games both at home and with a community, and low for the non-watchers. Beside differences in personalities, some main influencing factors were also found for people's watching/not watching decisions and all these factors were categorized as economic, social, cultural, personal, motivational, and environmental factors.
Keywords: Spectator Behaviors; Spectator Characteristics; Football's Entertainment Value; Game Watching; Business & Economics